Socio- economic impact of Krishi Mahotsav on Beneficiary Farmers of Gujarat - S.P.Pandya , M. R. Prajapati and K. P. Thakar, (Indian Journal of Extension Education, 2015)
Transfer of scientific technologies from research station to farmers' fields plays the vital role for rural development andrural upliftment. The government of Gujarat organizes Krishi Mahotsav every year before monsoon. It is a uniqueapproach of transfer of technology in the whole rural area. There are 18000 villages in Gujarat and Krishi Rath equippedwith scientific technology information through posters, panels, TV moves in every village. The scientists of agriculturaluniversities are appointed to deliver latest technical know-how. It was started in 2005 and designed for the benefits offarming community for one month duration. Eight Krishi Mahotsav have been completed till this study. The present studywas conceived with a general objective of assessing the socio economic impact of Krishi Mahotsav on beneficiary farmersas a result of participating in Krishi Mahotsav. Four districts of Gujarat state Banaskantha, Mahesana, Sabarkantha andKachchh were randomly selected for this study. The results revealed that majority of beneficiary farmers were found inmedium category of socio-economic impact as a result of participation in Krishi Mahotsav. About aspect-wise socioeconomic impact, majority of beneficiary farmers (43.33 %) have increased their cultivation land as a result ofparticipating in Krishi Mahotsav and 95 per cent beneficial farmer have increased their annual income per hectare.According to the, opinion of the beneficiary farmers 57.08 per cent of them had increased their saving and investment,67.92 per cent of them increased their social status and 72.50 per cent of the beneficiary farmers increased their socialrelationship through participation in Krishi Mahotsav.